A CRITICAL DISCOURSE ANALYSIS OF AN ESSAY: EMPLOYING RUTH WODAK’S MODEL - Ameer Ali; Mohammad Ibrahim Soomro (Elite : English and Literature Journal, 2020)
Critical Discourse Analysis demystifies power mechanisms operating in different kinds of discourse. It sets forth hidden discourses and meanings for common people. Besides, the current research assignment has studied Bernard Lewis’ essay: The Roots of Muslim Rage using Ruth Wodak’s Discourse Historical Model (2004). Moreover, the researchers have employed purposive sampling as a research design to collect the data. The research is qualitative as it answers the research questions using Wodak’s model. The purpose of this research was to expose hermeneutic interpretations of orientalist discourse that reflect implausible thinking about Muslims. However, much work has been done on discourse of orientalism, yet from Wodak’s point of view much work is to be done; hence, the current research paper has also contributed to the field of critical discourse analysis. The subjectification of the Muslims through oriental norms is the main theme in Lewis’ essay as revealed by analysing lexical and syntactic units. Thus, the current research has concluded the findings in accordance with the research questions and research objectives.